A-179 The Relationship Between Self-Rated Everyday Memory and Cognitive Status Among Older Adults. (28th August 2020) - M, Vasquez; J, Helphrey; A, Sandlin; L, Bennett-Leleux; R, Donnell; T, Glover; C, Markey; J, Moore; M, Barnett
Abstract: Objective: Neuropsychologists often supplement performance-based measures of cognition with self-report questionnaires. One questionnaire—the Measurement of Everyday Cognition (ECog)—has shown promise in differentiating between impaired and non-impaired populations; however, little research has been done specifically on the memory items from the shortened version: the ECog-12. The purpose of this study was to examine the extent to which the Ecog-12 Memory subscale can predict actual cognitive function as measured by a performance-based screening test. Method: Older adults (ages 55–90; n = 74) completed the ECog-12 and were administered the Mini-Mental Status Exam—2nd Edition (MMSE-2), with scores dichotomized into normal function and impaired function. Results: Binary logistic regression found that the ECog-12 Memory subscale items explained between 57% and 87% of variance in normal/impaired MMSE-2 scores and accurately classified 79.7% of cases. Conclusion: Brief self-report measures of everyday memory functioning are sensitive to cognitive decline among older adults.